2006
DOI: 10.1677/joe.1.06751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periconceptional undernutrition and gender on hypothalamic–pituitary–adrenal axis function in young adult sheep

Abstract: Glucocorticoids are proposed to act as intermediary factors that transcribe the developmental programming sequelae of maternal nutrient restriction (NR). Periconceptional undernutrition of sheep markedly activates fetal hypothalamicpituitary-adrenal (HPA) axis activity leading to preterm birth, while transient undernutrition during late gestation in sheep programs adult HPA axis function. To date, no study has examined resting or stimulated HPA axis function in young adult offspring following a periconceptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 59 publications
8
48
2
Order By: Relevance
“…Responses are variable (due, in part, to inconsistency between studies in time at which the offspring were assessed), but do suggest some sex-specific variation, as seen in young adult sheep (e.g. Gardner et al 2006), and differences in responses when lambs are younger or older. Studies in cattle are very scarce, but Lay et al (1997) showed that repeated transportation of Brahman cows during gestation increased the cortisol response of the progeny to an acute restraint stress.…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%
“…Responses are variable (due, in part, to inconsistency between studies in time at which the offspring were assessed), but do suggest some sex-specific variation, as seen in young adult sheep (e.g. Gardner et al 2006), and differences in responses when lambs are younger or older. Studies in cattle are very scarce, but Lay et al (1997) showed that repeated transportation of Brahman cows during gestation increased the cortisol response of the progeny to an acute restraint stress.…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%
“…As in the placenta (see above), this response is mediated by an increase in both gene expression for the glucocorticoid receptor and reduced action of the enzyme 11b-hydroxysteriod dehydrogenase type 2 which occurs in a range of newborn tissues including heart, kidney, liver and lungs (Whorwood et al, 2001). These changes would be predicted to enhance glucocorticoid action even in the absence of any change in plasma cortisol (Gardner et al, 2006). These have no immediate adverse effect on the offspring and persist in some tissues into juvenile life when offspring are raised in an outdoor-free living environment.…”
Section: Effect Of Maternal Nutrient Restriction Between Early-to-midmentioning
confidence: 99%
“…Brief undernutrition for 10 but not 20 days during late gestation altered the HPA function in adult offspring, further emphasizing the fact that the timing, type, and duration of fetal nutrient restriction are each important in determining the nature of the fetal adaptive responses and their pathophysiological sequelae in later life (Bloomfield et al 2003). More recently periconceptional undernutrition was shown to exert a minor influence on HPA axis function in young adult sheep (Gardner et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…In sheep, maternal cortisol changes are related to the timing when feed restriction is imposed. Late-gestation undernutrition resulted in elevated maternal cortisol concentrations , while early-to mid-gestation or periconceptional undernutrition resulted in reduced or unchanged cortisol levels respectively (Bispham et al 2003, Gardner et al 2006.…”
Section: Introductionmentioning
confidence: 99%